Demographic Trends in Nonmetropolitan America - Daryl Hobbs (Journal of Research in Rural Education, 1994)
Rural America is dynamic: continuously affected by changes that have influenced who and how many live there; and where and how they earn their living, go to school, shop, and obtain health care services. As society has modernized, rural America has been swept along in the process, losing general stores, one-room schools, family farms, and many of the traditions, values, and customs that have produced distinctive rural life styles. These changes have been so profound socially, economically, and demographically that rural and urban have lost much oftheir meaning. Indeed, differences between rural "then" and "now" often are greater than present differences between rural and urban.